2020
DOI: 10.1038/s41598-020-73164-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prognostic value of stemness-related genes in breast cancer patients

Abstract: Breast cancer (BC) is currently one of the deadliest tumors worldwide. Cancer stem cells (CSCs) are a small group of tumor cells with self-renewal and differentiation abilities and high treatment resistance. One of the reasons for treatment failures is the inability to completely eliminate tumor stem cells. By using the edgeR package, we identified stemness-related differentially expressed genes in GSE69280. Via Lasso-penalized Cox regression analysis and univariate Cox regression analysis, survival genes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Previous study suggested that GRB7 overexpression was an independent factor of poor prognosis ( 34 ). Furthermore, we observed several arm-level deletions of BC tumor suppressor genes and favorable BC prognostic genes in patients who failed to achieve pCR, including CDKN2C ( 35 ), EPS15 ( 36 ), etc. Of note, there were a considerable number of genes related to BC development and progression in the regions where deletions were identified, including CDKN2C , EPS15 , CBL , etc.…”
Section: Discussionmentioning
confidence: 95%
“…Previous study suggested that GRB7 overexpression was an independent factor of poor prognosis ( 34 ). Furthermore, we observed several arm-level deletions of BC tumor suppressor genes and favorable BC prognostic genes in patients who failed to achieve pCR, including CDKN2C ( 35 ), EPS15 ( 36 ), etc. Of note, there were a considerable number of genes related to BC development and progression in the regions where deletions were identified, including CDKN2C , EPS15 , CBL , etc.…”
Section: Discussionmentioning
confidence: 95%
“…Xu et al also established an NPR3-containing 7-IRG risk model, and the risk score presented excellent predictive ability in gastric cancer and revealed the status of the tumour immune microenvironment 32 . Similarly, Wang et al proposed a model consisting of 4 stemness-related genes (PSMB9, CXCL13, NPR3, and CDKN2C) to identify targets of BC stem cells and improved the therapeutic effect 33 . In our study, NPR3 with the other 6 IRGs constituted an excellent model with excellent prognostic and TME-predictive value for BC.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that NPR3 might be a potential biomarker in breast cancer outcome prediction. 31 The identification of novel stage-specific biomarkers has attracted increasing attention from researchers in CRC progression. A previous study have identified that DYNC1H1, GRIN2A, and GRM1 as new driving genes for CRC stage II progression, IGF1R, CPS1, SPTA1, and DSP as new hub driving genes for CRC stage III progress, and GSK3B, GGT1, and EIF2B5 as new hub driving genes for CRC stage IV.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that NPR3 might be a potential biomarker in breast cancer outcome prediction. 31…”
Section: Discussionmentioning
confidence: 99%